Multi-approach methods to predict cryptic carbapenem resistance mechanisms in Klebsiella pneumoniae detected in Central Italy - Cornacchia, Alessandra; Janowicz, Anna; Centorotola, Gabriella; Saletti, Maria Antonietta; Ranieri, Sofia Chiatamone; Ancora, Massimo; Ripà, Paola; Cammà, Cesare; Pomilio, Francesco; Chiaverini, Alexandra (Frontiers in Microbiology, 2023)
The rapid emergence of carbapenem resistant Klebsiella pneumoniae (Kp) strains in diverse environmental niches, even outside of the clinical setting, poses a challenge for detection and the real-time monitoring of novel antimicrobial resistance trends using molecular and whole genome sequencing-based methods.The aim of our study was to understand cryptic resistance determinants responsible for the phenotypic carbapenem resistance observed in strains circulating in Italy by performing a combined approach using whole genome sequencing (WGS) and genome wide association study (GWAS). In this study, we collected 303 Kp strains from and outside of clinical settings between 2018-2022 in Abruzzo Region, Italy. The antimicrobial resistance profile of all isolates was assessed using both phenotypic and bioinformatic methods. We identified 11 strains resistant to carbapenems, which did not carry any known genetic determinants explaining their phenotype. The GWAS results showed that incongruent carbapenem resistant phenotype was associated specifically with strains with two capsular types, KL13 and KL116 including genes involved in the capsule synthesis, encoding proteins involved in the assembly of the capsule biosynthesis apparatus, capsule-specific sugar synthesis, processing and export, polysaccharide pyruvyl transferase and lipopolysaccharide biosynthesis protein. These preliminary results confirmed the potential of GWAS to identify genetic variants, present in KL13 and KL116, that could be associated with carbapenem resistance traits in Kp. The implementation of advanced methods such as GWAS with increased antimicrobial resistance surveillance will potentially improve Kp infection treatment and patient outcomes.